1996
DOI: 10.1136/ard.55.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activators and their inhibitors in synovial fluids from normal, osteoarthritis, and rheumatoid arthritis knees.

Abstract: Objectives-To establish baseline concentrations of plasminogen activators and their inhibitors in normal knee synovial fluids, and to compare them with weli characterised osteoarthritis (OA) and rheumatoid arthritis (RA) knee fluids. Methods-A total of 26 normal subjects, 71 patients with OA, and 17 patients with RA underwent knee aspiration. Patients with OA were subclassified according to presence ofnodal generalised OA (NGOA) and synovial fluid calcium pyrophosphate crystals. Clinical assessment of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…In previous studies, the expression of IL-17F, PAs, and PAI-1 increased in RA synovial tissue 11,25) . However, the effects of IL-17F on PAs and PAI-1 expression were not reported in the synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the expression of IL-17F, PAs, and PAI-1 increased in RA synovial tissue 11,25) . However, the effects of IL-17F on PAs and PAI-1 expression were not reported in the synovial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that nicotine promotes extracellular matrix destruction by increasing tPA expression in human osteoblastic Saos-2 cells 23) , and that nicotine and lipopolysaccharide (LPS) contribute to bone resorption by increasing tPA production in osteoblasts 24) . In studies of RA and cartilage, it was reported that concentrations of tPA, uPA, and PAI-1 in synovial fluids are significantly higher in RA patients 25) and that IL-1 increases the expression of tPA, uPA, and PAI-1 in chondrocytes 26,27) . However, the effects of IL-17F on cartilage matrix turnover via the plasminogen/plasmin pathway are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Belcher et al reported that synovial fluid levels of suPAR were raised in patients with osteoarthritis (OA) and rheumatoid arthritis (RA) as compared to healthy controls [77]. Since then, uPAR and suPAR have been investigated both in humans and in animal models of OA [77][78][79][80][81], RA [26,77,78,80,[82][83][84][85][86][87][88], gouty arthritis [89], and ankylosing spondylitis [90].…”
Section: Supar As a Biomarker In Sle And Other Rheumatic Diseasesmentioning
confidence: 99%
“…Since then, uPAR and suPAR have been investigated both in humans and in animal models of OA [77][78][79][80][81], RA [26,77,78,80,[82][83][84][85][86][87][88], gouty arthritis [89], and ankylosing spondylitis [90]. There are also observations on involvement of the uPAR system in systemic sclerosis [91][92][93] and Behçet's disease [94].…”
Section: Supar As a Biomarker In Sle And Other Rheumatic Diseasesmentioning
confidence: 99%
“…The plasminogen activator (PA) system is a general proteolytic enzyme system that has been suggested to play an important role in the degradation of the extracellular matrix (ECM) during the development of RA (14,15). Plasmin, the key component of the PA system, is generated by conversion of the precursor plasminogen by 2 distinct physiologic PAs, tissue PA (tPA) and urokinase PA (uPA) (16).…”
mentioning
confidence: 99%